Dekonstruksi Sistem Rekrutmen Lembaga Pendidikan Islam dari Person-Organisation Fit Menuju Person-Ideological Fit - Khairunnafi; Saiful Hadi; Tobi (Kartika: Jurnal Studi Keislaman, 2026)
The governance and recruitment of Human Resources (HR) within Islamic educational institutions are frequently confined to abstract-normative paradigms and traditional patronage practices, thereby undermining meritocratic principles. This research aims to simultaneously deconstruct and reconstruct the talent acquisition model in Islamic educational institutions through analytical, academic, and professional critical perspectives. This study employs a qualitative methodology featuring a library research design. Secondary data acquisition was executed via purposive text selection of reputable literature (2016–2026), subsequently analysed using the interactive model of Miles, Huberman, and Saldaña, and validated through intertextual source triangulation techniques. The findings assert that recruitment effectiveness necessitates the conversion of theological-spiritual values into measurable performance indicators, the integration of digital agility, and the utilisation of the Hersey-Blanchard readiness taxonomy as a behaviour-based selection instrument to mitigate kinship bias. Theoretically, this study contributes to broadening the Person-Organisation Fit (P-O Fit) concept into a Person-Ideological Fit. The practical implications compel Islamic educational institutions to transform their ad-hoc seasonal recruitment paradigms into structured human capital management to ensure the sustainability of organisational quality